Synthesis, Molecular Docking Study and Antimicrobial Evaluation of Some 1,2,4-Triazole Compounds - Muhammad-Ali, Munther Abduljaleel; Jasim, Ekhlas Qanber; Mohammed, Abeer Issa (Indian Journal of Pharmaceutical Education and Research, 2025)
Aim: The objective of this study is synthesis of 1,2,4-triazole derivatives, evaluation there in vitro antimicrobial activity and showing the molecular docking. Materials and Methods: Two series of 5-alkylthio-3-aryl-4-phenyl-1,2,4-triazoles were successfully synthesized. The 1,2,4-triazole thiol was produced via cyclization reaction using the hydrazide compounds (2-hydroxybenzohydrazide and 5-bromofuran-2-carbohydrazide), which were then employed as nucleophilic species to attract various kinds of alkyl halides to synthesis the final compounds. All produced compounds underwent spectroscopic characterization and tested their antibacterial and antifungal activities. With synthetic ligands, molecular docking studies were conducted against the proteins 1AJ0, 1JIJ, and 4ZA5 to identify the crucial interactions underlying antimicrobial activity. Results: UV-visible, FTIR, 1H-NMR and CHNS analysis were confirmed the chemical structures and purity. Initial antibacterial screening results showed that several produced compounds 1e, 1f, 2e, and 2f have good inhibitory effects, whilst some compounds 2e demonstrated high antifungal activity when compared to the control drug fluconazole. Two active substances, 1e and 2e, showed a moderate level of toxicity, with LD50 values of 3.5 and 2.3 g/kg, respectively. The strongest compounds, 1e, 1f, 2e, and 2f, demonstrated high binding energy antibacterial and antifungal activity, which were supported by docking analysis. Conclusion: Triazole derivatives were synthesized by multi-reaction steps with high yields. Some synthesized triazole derivatives showed promising antibacterial and antifungal activities as compared with parent compounds and standard drugs. The results of antimicrobial activities of compounds were enhanced by good affinity of molecular docking of these compounds with the active site of proteins as compared with standard drugs amoxicillin and fluconazole.
Keywords: Triazole; Antibacterial; Antifungal; Molecular docking; MIC; Modification of drug